Interrelationship between food intake & nutritional anaemia among the children studied in a tertiary care hospital in Dhaka city (Journal of Paediatric Surgeons of Bangladesh, 2018)
This study was carried out on 128 children of which 80 were male & 48 were female admitted in Paediatric department of DMCH. They were 1 to 12 yrs. 31, 27, 24 and 46 children were of 1-3 yrs, 4-6 yrs, 7-9 yrs & 10-12 yrs age group respectively. A cross sectional sample survey study was carried out. Main variables were age, family size, monthly family income, parents education & occupation Hb and PCV levels.58% children were illiterate group which also includes less than 5 yrs children. 12% were at primary level & 30% were at high school level. The children of 1-3yrs, 4-6yrs, 7- 9yrs & 10-12yrs age groups took an average of 290, 285, 505 & 555 gm foods/child/day. Cereals intake was highest (67.7%) in comparison to other foods. Consumption of meat, fruits, fats & milk was very low. Iron intake was found more than requirement & Vit-C intake was found lowest of the nutrients requirement.The study revealed the children met protein, iron, folic acid, Vit-A, Vit-B12, Vit-C, Vit-B2 , Vit-B6 , Zinc & Copper 70.79%, 122.2%, 92%, 72%, 68.5%, 55%, 83%, 57%, 89% & 82% respectively of the requirements. Less than 50% of the requirements of iron, protein, Vit-A, Vit-C, Vit- B2 & folic acid is met by 15%, 50.5%, 39%, 45%, 12% & 29% children respectively.Mean Hb level is found (10.39±2.23)gm/dl of blood & ranges from 4.7gm/dl to 12.9gm/dl & mean PCV level is found (30.1±2.21) percent & ranges from 13.63% to 37.41%. According to Nutrition Survey of Rural Bangladesh 1981- 82 & WHO, 1972 28,29 Hb leve